Tratamento de água residuária de fecularia em reator anaeróbio com leito de pedras de calcário dolomítico - Palma, Denise (2012)
The cassava processing for starch or flour production generates some wastewater (manipueira) with high organic load and toxic compounds, which cause environmental degradation. In the western Paraná region, there are several starch factories, so its waste generation is a concern for the correct treatment and disposal. Thus, anaerobic reactors are a cost-effective option to treat manipueira since its waste has an easy biological degradation. However, anaerobic digestion requires the monitoring of management conditions as the steady ratio of volatile acidity/total alkalinity. Usually, when this ratio becomes high enough and makes impossible the conversion process of chemical compounds in biogas, substances that provide alkalinity to the medium are used. The utilization of lime stone in manipueira anaerobic treatment was the aim of this trial, whose specific goals were to evaluate the limestone efficiency as alkalizing agent, the efficiency system on organic matter removal, solids removal and biogas production and the potential use of the reactor effluent as a biofertilizer. An anaerobic horizontal reactor was used with the following measures: length:width ratio 1:6; 15.9 L total volume and 7.95 L net volume. The studied reactor had five sampling points, distributed along its form, whose main point was used as an output for the produced biogas. Biogas was stored in two gasometers of floating dome type. These ones, in turn, had coupled thermometers, pressure gauges and valves to release the daily biogas. The reactor was kept under water bath at nearly 27 oC. The inoculum was sludge that came from a similar reactor used for manipueira treatment. The limestone contained 27.33% CaO and 22.97% MgO that were standardized according to the size, so the used limestone ranged from 24.5 to 38.1 mm. The mass of stones / manipueira volume ratio was 50%. The reactor supplying occurred under sequence and manipueira volume was distributed throughout the day by a peristaltic pump connected to a timer. The organic loads were estimated based on organic load concentration of gross manipueira, according to the Chemical Oxygen Demand value. The applied organic loads were: 1.23, 1.54, 1.84, 2.45, 3.40, 4.96, 6.01, 8.11, 10.14, 12.39, 14.79 and 16,43 g COD Lr -1 d-1, with their respective hydraulic retention times: 10, 7.99, 6.65, 5.0, 4.42, 1.69, 1.39, 2.21, 1, 77, 1.45, 0.88 and 0.80 days. The Ca2+ ion concentrations in the reactor effluent increased while Mg2+ ion concentrations decreased. TA, pH, VA and VA/TA averages were 6.69, 882.54 mg CaCO3 L-1, 221.55 mg CH3COOH L-1 and 0.22, respectively. VFA was detected in the reactor effluent. TS, FTS, VTS and COD removals were 84.01, 35.98, 93.43 and 86.88%, respectively, and the average of specific biogas production was 0.12 L biogas g CODremoved -1. The reactor effluent showed higher overall averages of N, P and K concentrations as 162.24, 14.82 and 520.29 mg L-1. At last, it can be concluded that the system operated under optimal conditions for methanogenic bacteria activity, however, the specific biogas production was lower than expected. The solids and organic matter removals were satisfactory according to an anaerobic treatment and the effluent can be used as biofertilizer